2015
DOI: 10.1016/j.ssi.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Mapping electrochemically driven gas exchange of mixed conducting SrTi0.7Fe0.3O3−δ and Ce0.8Gd0.2O1.9 thin films by 18O tracer incorporation under reducing atmosphere

Abstract: Thermally and electrochemically driven 18O tracer exchange experiments in H2/H218O atmosphere were performed on SrTi0.7Fe0.3O3 − δ and Ce0.8Gd0.2O2 − δ thin films on single crystalline YSZ substrates. Noble metal current collectors were deposited on both films and electrochemically polarized during the exchange experiment. The resulting tracer distribution was analyzed by spatially resolved secondary ion mass spectrometry. Increased tracer fraction near the current collectors was found under cathodic polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The main conductance increase of the non-etched Ni/TiO 2 /YSZ samples is thus caused by the much larger active area for the electrochemical reaction due to in-plane electron conduction in TiO 2 . A very similar situation can be found for ceria based mixed conducting anodes [37,38]. The rate-limiting process is probably a combination of lateral transport of electrons and electrochemical reaction at the surface of mixed conducting TiO 2 .…”
Section: Discussionsupporting
confidence: 66%
“…The main conductance increase of the non-etched Ni/TiO 2 /YSZ samples is thus caused by the much larger active area for the electrochemical reaction due to in-plane electron conduction in TiO 2 . A very similar situation can be found for ceria based mixed conducting anodes [37,38]. The rate-limiting process is probably a combination of lateral transport of electrons and electrochemical reaction at the surface of mixed conducting TiO 2 .…”
Section: Discussionsupporting
confidence: 66%
“…Mapping of 18 O exchange on similar electrodes revealed that the Pt film is not permeable for oxygen and therefore reduces the electrochemically active area of the STF electrode. 26 At the triple phase boundary (TPB), however, the oxygen exchange is catalyzed by the platinum, 42,44 causing the much smaller electrode arc with Pt on top. The contributions of the STF surface and the TPB can be separated by measuring electrodes of all 9 geometries shown in Figure 1e.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in an attempt to measure diffusion coefficients of sulphur in GDC by means of ToF-SIMS, sulphur incorporation experiments were performed on macroscopic GDC 10 polycrystals over several days of exposure. To increase the rate of surface sulphur incorporation and to suppress possible back reactions with water [ 44 , 45 ], a dry hydrogen atmosphere was chosen. The resulting depth profiles are plotted in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%